Urban green and blue spaces for influencing physical activity in the United Kingdom: A narrative review of the policy and evidence - Callum Leese; Hussain Al‐Zubaidi (Wiley, 2024)
Abstract Introduction With the rapid growth of urbanization globally and in the UK, increasing attention is now being directed towards urban green spaces (UGS). The appeal of UGS to policymakers lies in their capacity to address multiple policy objectives, including improving physical and mental wellbeing, mitigating noncommunicable diseases (NCDs), combating climate change through carbon sequestration, providing climate adaptation measures, and enhancing biodiversity. Method This narrative review gives an overview of the current literature and UK policy relating to urban green and blue spaces, with a particular focus on the use of UGS to increase physical activity levels. Results UGS have a profound impact on public health, with evidence indicating their positive effect on both physical and psychological health. Thirty‐eight percent of adults in the UK do not live within 15 minutes of UGS, so policy makers at national and international level are aiming to address this gap. One reason for the health benefits of UGS is associated increased physical activity, a vital component needed to address the burden of non‐communicable disease. To effectively harness UGS to promote physical activity various factors must be considered; proximity and diversity of urban green spaces, and the presence of suitable infrastructure features. Tailoring UGS to meet the needs and preferences of different population demographics is essential, as is ensuring safety, and addressing barriers to access particularly for lower socio‐economic groups. The careful planning of UGS must avoid potential gentrification effects and displacement of vulnerable communities, whilst utilising the equigenic nature of UGS. Conclusions To create a brighter future and capitalize on the potential of UGS, a collaborative approach is needed, involving communities, local governments, and national authorities. Primary‐care professionals, represented by organizations like the Royal College of General Practitioners (RCGP), can play a crucial role in advocating for UGS and physical activity, promoting their use, and providing guidance and support.